VISUALISASI BODY-SHAMING DALAM FOTOGRAFI EKPRESI - Sanjaya, I Gusti Katon Dwi; Darmawan, I Dewa Made; Nindhia, Cokorda Istri Puspawati (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
This project is entitled